Douglas Hyde : a maker of modern Ireland - Dunleavy, Janet Egleson (University of California Press, 1991)
In 1938, at an age when most men are long retired, Douglas Hyde (1860-1949) was elected first president of modern Ireland. The unanimous choice of delegates from all political factions, he was no stranger to public life or to fame. Until now, however, there has been no full-scale biography of this important historical and literary figure. Known as a tireless nationalist, Hyde attracted attention on both sides of the Atlantic from a very early age. He was hailed by Yeats as a source of the Irish Literary Renaissance; earned international recognition for his contributions to the theory and methodology of folklore; joined Lady Gregory, W.B. Yeats, George Moore, and Edward Martyn in shaping an Irish theater; and as president of the Gaelic League worked for twenty-two years on behalf of Irish Ireland. Yet in spite of these and other accomplishments Hyde remained an enigmatic figure throughout his life. Why did he become an Irish nationalist? Why were his two terms as Irish Free State senator so curiously passive? Why, when he had threatened it earlier, did he oppose the use of physical force in 1916? How did he nevertheless retain the support of his countrymen and the trust and friendship of such a man as Eamon de Valera? Douglas Hyde: A Maker of Modern Ireland dispels for the first time the myths and misinformation that have obscured the private life of this extraordinary scholar and statesman.